Perancangan Set Meja Dan Kursi Dari Limbah Kayu Untuk Café - Amadea Belinda; Grace Mulyono; Poppy Firtatwentyna Nilasari (Intra, 2020)
The nature of Indonesia, which has made us proud, is a country rich in natural resources that have been passed down through many variations, the design of interior products that the author is making is expected to be able to utilize the remnants of wood by perhaps being able to help increase the amount of wood waste littered in Indonesia especially the city of Surabaya. This table and chair set will be sold at an affordable price making it suitable for middle-low-budget cafes. With this solution, it is hoped that it can help our earth to experience the problem of garbage or waste that cannot be recycled so that the community is motivated to help and collect wood waste that can still be recycled to produce useful and beneficial products.